Analysis of the characteristics of phosphine production by anaerobic digestion based on microbial community dynamics, metabolic pathways, and isolation of the phosphate-reducing strain - Fan, Yimin; Niu, Xiaojun; Zhang, Dongqing; Lin, Zhang; Fu, Mingli; Zhou, Shaoqi (Chemosphere, 2021)
Although phosphine is ubiquitously present in anaerobic environments, little is known regarding the microbial community dynamics and metabolic pathways associated with phosphine formation in an anaerobic digestion system. This study investigated the production of phosphine in anaerobic digestion, with results indicating that phosphine production mainly occurred during logarithmic microbial growth. Dehydrogenase and hydrogen promoted the production of phosphine, with a maximum phosphine concentration of 300 mg/m3. The abundance of Ruminococcaceae and Escherichia was observed to promote phosphine generation. The analysis of metabolic pathways based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) and the MetaCyc pathway database revealed the highest relative abundance of replication and repair in genetic information processing; further, the cofactor, prosthetic group, electron carrier, and vitamin biosynthesis were observed to be closely related to phosphine formation. A phylogenetic tree was reconstructed based on the neighbor-joining method. The results indicated the clear evolutionary position of the isolated Pseudescherichia sp. SFM4 strain, adjacent to Escherichia, with a stable phosphate-reducing ability for a maximum phosphine concentration of 26 mg/m3. The response surface experiment indicated that the initial optimal conditions for phosphine production by SFM4 could be achieved with nitrogen, carbon, and phosphorus loads of 6.17, 300, and 10 mg/L, respectively, at pH 7.47. These results provide comprehensive insights into the dynamic changes in the microbial structure, isolated single bacterial strain, and metabolic pathways associated with phosphine formation. They also provide information on the molecular biology associated with phosphorus recycling.
Keywords: fosfiny; Escherichia; Hydrogen; fosfáty; fosfor; anaerobióza; metabolické sítě a dráhy; bioreaktory; Nitrogen; Phosphorus; dusík; Phosphines; odpadní vody; fylogeneze; Metabolic Networks and Pathways; Anaerobiosis; Phosphates; Sewage; mikrobiota; Microbiota; Clostridiales; vodík; Bioreactors; Phylogeny